Duraplasty and Obex Exploration Compared with Bone Only Decompression for Chiari I Malformation in Children: Retrospective Review of Outcomes and Complications. (16th November 2020) - Ene, Chibawanye I; Wang, Anthony C; Collins, Kelly; Bonow, Robert H; McGrath, Lynn B; Durfy, Sharon; Barber, Jason; Ellenbogen, Richard G
Abstract: INTRODUCTION: Some pediatric Chiari I malformation (CM-I) patients remain asymptomatic, while others present with debilitating symptoms necessitating surgery. Surgery aims to restore normal cerebrospinal fluid flow, including increasing the posterior fossa volume via bone decompression only, or bone decompression with duroplasty, with or without obex exploration. Indications for duroplasty and obex exploration following bone decompression remain controversial. METHODS: A retrospective review was conducted of medical records of 294 CM-I patients (<20 years), operated on at a single institution between 2001–2015 by the senior author (RGE). Imaging findings of tonsillar descent, associated syrinx (syringomyelia or syringobulbia), basilar invagination, clinical assessment of CM-I attributable symptoms, and scoliosis were recorded. Clinical outcomes, including syrinx resolution, symptom resolution, impact on scoliosis progression and complications were compared for 3 groups: bone only/posterior fossa decompression (PFD), with duraplasty (PFDwD), with duraplasty and obex exploration (PFDwDO). RESULTS: Nearly half of patients (141/294, 48%) had a syrinx. PFD was performed in 27% of patients (78/294); PFDwD in 17% of patients (51/294); PFDwDO in 56% of patients (165/294). Mean follow-up was 36 months (±35). Relative to PFD, PFDwDO was associated with significantly higher likelihood of syrinx resolution (HR 2.68, P = .007) and trended toward earlier symptom resolution (HR = 1.86, P = .110). Scoliosis outcomes did not differ between the 3 groups ( P = .289). Complications were not significantly higher when duroplasty or obex exploration was performed ( P = .09). CONCLUSION: In our series, for pediatric patients with CM-I presenting with syrinx, with or without scoliosis, PFDwDO significantly increased the likelihood of surgical success in terms of syrinx resolution without increased complications.